A Highly Conductive MOF of Graphene Analogue Ni3(HITP)2 as a Sulfur Host for High‐Performance Lithium–Sulfur Batteries. Issue 44 (13th September 2019) - Cai, Dong; Lu, Mengjie; Li, La; Cao, Junming; Chen, Duo; Tu, Haoran; Li, Junzhi; Han, Wei
Abstract: Lithium–sulfur (Li–S) batteries have been considered as one of the most promising energy storage systems owing to their high theoretical capacity and energy density. However, their commercial applications are obstructed by sluggish reaction kinetics and rapid capacity degradation mainly caused by polysulfide shuttling. Herein, the first attempt to utilize a highly conductive metal–organic framework (MOF) of Ni3 (HITP)2 graphene analogue as the sulfur host material to trap and transform polysulfides for high‐performance Li–S batteries is made. Besides, the traditional conductive additive acetylene black is replaced by carbon nanotubes to construct matrix conduction networks for triggering the rate and cycling performance of the active cathode. As a result, the S@Ni3 (HITP)2 with sulfur content of 65.5 wt% shows excellent sulfur utilization, rate performance, and cyclic durability. It delivers a high initial capacity of 1302.9 mAh g −1 and good capacity retention of 848.9 mAh g −1 after 100 cycles at 0.2 C. Highly reversible discharge capacities of 807.4 and 629.6 mAh g −1 are obtained at 0.5 and 1 C for 150 and 300 cycles, respectively. Such kinds of pristine MOFs with high conductivity and abundant polar sites reveal broad promising prospect for application in the field of high‐performance Li–S batteries. Abstract : A highly conductive metal–organic framework of pristine Ni3 (HITP)2 with hierarchical pores and abundant polar sites serves as an advanced sulfur host for lithium–sulfur batteries. In conjunction with carbon nanotube additives, matrix conduction networks can be constructed which endow the fabricated battery with enhanced rate and cycling performance.